Measuring Fiscal Multipliers in Egypt: Applying the Bucket and SVAR Approaches - Abdel-Haleim, Sahar M. (The Arab Journal of Administration, 2024)
Contrary to the Keynesian view, quantifying the fiscal multipliers in Egypt yields small magnitude using empirical and non-empirical approaches. The effectiveness of fiscal policy is analyzed using two approaches. Firstly, the ‘Bucket approach’ deduces the size of fiscal multipliers within the framework of several structural factors that are believed to have a significant effect in determining the size of fiscal multiplier. This represents the first such study that applies the “Bucket approach” in the case of Egypt. Secondly, the Structural Vector Auto-Regression (SVAR) approach is estimated over the period (2005/06 – 2017/18) with quarterly data. This high-frequency data enables identifying the SVAR model through imposing the contemporaneous restrictions. The model includes government expenditures, tax revenues, output and interest rate in real terms. The findings of the ‘Bucket approach’ and SVAR were consistent and confirm a limited Keynesian demand push effect. Government spending proves to be much more effective tool than the tax revenues. JEL: E60; H30; C32